Inhibition of Defocus-Induced Myopia in Chickens - Woods, Jill; Guthrie, Sarah E.; Keir, Nancy; Dillehay, Sally; Tyson, Mark; Griffin, Richard; Choh, Vivian Cheng-Pei; Fonn, Desmond; Jones, Lyndon W.; Irving, Elizabeth (Association for Research in Vision and Ophthalmology, 2013)
Purpose.: To determine the effect of wearing a lens with a unique peripheral optical design on the development and progression of defocus-induced myopia in newly hatched chickens.Methods.: Eighty-five newly hatched chickens underwent bilateral retinoscopy and A-scan ultrasound to determine their refractive error and axial length. They were randomly divided into Control and two Test groups, in which each chicken was fitted with a goggle-lens over the right eye, with the left eye remaining untreated. The Control group wore a lens of power −10.00 diopters (D) of standard spherical optical design. The two Test lenses both had a central optical power −10.00 D, but used different peripheral myopia progression control (MPC) designs. For all groups, retinoscopy was repeated on days 3, 7, 10, and 14; ultrasound was repeated on day 14. Results.: On day 0 there was no statistical difference in refractive error (mean +6.92 D) or axial length (mean 8.06 mm) between Test and Control groups or treated and untreated eyes (all P > 0.05). At day 14, 37 (43.5%) of 85 chickens had not experienced goggle detachment and were included in the final analyses. In this cohort there was a significant refractive difference between the treated eyes of the Control group (n = 17) and those of Test 1 (n = 14) and Test 2 (n = 6) groups (both P < 0.01): Control −4.65 ± 2.11 D, Test 1 +4.57 ± 3.11 D, Test 2 +1.08 ± 1.24 D (mean ± SEM). There was also a significant axial length difference (both P < 0.01): Control 10.55 ± 0.36 mm, Test 1 9.99 ± 0.14 mm, Test 2 10.17 ± 0.18 mm. Conclusions.: Use of these unique MPC lens designs over 14 days caused a significant reduction in the development of defocus-induced myopia in chickens; the degree of reduction appeared to be design specific.
Woods, J., Guthrie, S. E., Keir, N., Dillehay, S., Tyson, M., Griffin, R., … Irving, E. (2013). Inhibition of Defocus-Induced Myopia in Chickens. Investigative Opthalmology & Visual Science, 54(4), 2662. https://doi.org/10.1167/iovs.12-10742
Keywords: Myopia control; Emmetropization; Refractive error; Eye growth; Multifocal lens